Case report: reuse of tirofiban leads to very severe thrombocytopenia - Li, Yuqing; Qiu, Jiuchun; Gao, Yi; Li, Guangping (Frontiers in Cardiovascular Medicine, 2023)
Background Telofiban is a class of small molecule non-peptide tyrosine derivatives containing RGD sequences. It is the only platelet surface glycoprotein (GP) IIb/IIIa receptor antagonist (GPI) currently marketed in China. In patients with ST-segment elevation myocardial infarction(STEMI) who receive percutaneous coronary intervention (PCI) with a heavy thrombotic load, postoperative intravenous tirofiban can prevent complications of myocardial ischemia due to sudden coronary artery occlusion. With the increase in the clinical use of tirofiban, the number of adverse reactions related to thrombocytopenia induced by tirofiban has gradually increased. Still, most of them have thrombocytopenia after the first use. We report one case of very severe thrombocytopenia following the reuse of tirofiban. Case summary A 65-year-old man of Han nationality, 170 cm in height, 85 kg in weight, and 29.4 BMI, suffered from cerebral infarction 13 years ago and left with right limb movement disorder. Five days before this hospitalization, the patient underwent PCI, and three stents were implanted. After the operation, anti-platelet tirofiban and nadroparin calcium were given, and no thrombocytopenia was found. The patient still retains 80% stenosis due to anterior descending branches and plans to undergo PCI again half a month later. The patient with a history of hypertension, type 2 diabetes, diabetic nephropathy, and cerebral infarction usually took 100 mg of aspirin and 75 mg of clopidogrel, antiplatelet therapy, and had no history of food and drug allergy. One day after discharge, the patient suddenly felt chest tightness and wheezing. The laboratory showed hypersensitivity troponin 2.85 ng/ml (normal 0–0.0268 ng/ml), and the admission ECG showed ST-T changes in leads I, aVL, V5-V6. On the 6th day of hospitalization, PCI was performed, a stent was implanted in the proximal section of the anterior descending branch opening, and tirofiban(10 ug/kg, 3 min bolus, then 0.1 ug/kg/min) antiplatelet therapy was given after surgery. About 10 min after the tirofiban infusion, the patient suddenly shivered, accompanied by convulsions, accompanied by elevated body temperature (up to 39.4°C), accompanied by epistaxis and microscopic hematuria. An urgent blood test showed that the platelets dropped to 1 × 109/L, tirofiban and aspirin stopped immediately, and the antiplatelet therapy of clopidogrel was retained. After infusion of methylprednisolone sodium succinate and gamma globulin, the patient's platelets gradually recovered, and the patient was successfully discharged seven days later in stable condition. Conclusion This case is typical of severe thrombocytopenia caused by reusing tirofiban. This case may provide new insights into: 1. Patients who did not have thrombocytopenia after the first use of tirofiban may still have extremely severe thrombocytopenia after re-exposure to tirofiban. Routine platelet count monitoring and early identification of thrombocytopenia are the essential links. 2. Thrombocytopenia caused by re-exposure to tirofiban may have a faster onset, deeper degree, and slower recovery due to antibodies retained after the first exposure to tirofiban; 3. Platelet transfusions may not be necessary for patients with severe thrombocytopenia; 4. Immunosuppressants help suppress the body's immune response, promote platelet recovery, and can be reduced or discontinued when platelets rise and may be safe; 5. After tirofiban for PCI, continuing the maintenance dose of clopidogrel may be safe if the patient has no significant bleeding events.